Branding of the Kazakhstan territories - Saiken А.; Yerniyazova, Zh.N.; Shilmanova А.М.; Omarova, A.S. (BUKETOV BUSINESS REVIEW, 2017)
In the conditions of universal expansion of world economic relations, development of production capacities and, as a result, the formation of harsh conditions for competition, it is necessary to use new tools that allow the manufacturer to feel confident both on the domestic and foreign markets. One such tool is branding,which has become an integral part ofthe marketing programs for a long time of the most ofWestern compa- nies. The process of formation and development of market relations in the Republic of Kazakhstan is accom- panied by increasing competition between business entities, a constant change in the external and internal marketingenvironment, whichrequirestheimprovementofentrepreneurialandmarketingactivities tocreate, distribute and consume goods and services. First of all, the International Information Committee is responsi- ble for promoting and strengthening the positive image of our country abroad. In the globalised information world, there is the need to work out new approaches to creating a positive image for a country, which is why many countries are currently “re-branding” themselves to increase their recognisability and attractiveness. Kazakhstan is no exception, especially when we are trying to join the club of the top 50 most competitive countries in the world. Competitiveness starts with recognisability and the stability of a brand.